451 Dural Tears in Full-Endoscopic Unilateral Laminotomies for Bilateral Lumbar Decompression. (1st April 2022) - Kashlan, Osama; Bergquist, Julia; Prasse, Tobias; Greil, Madeline; Sivakanthan, Sananthan; Williams, John R.; Hofstetter, Christoph P.
Abstract : INTRODUCTION: Full-endoscopic unilateral laminotomy for bilateral lumbar decompression (ULBD) for spinal stenosis has proven benefits when compared to microscopic technique. Intraoperative laceration of the dura may be encountered and their optimal technique and effectiveness of full-endoscopic dural repair remains unclear. METHODS: For this analysis, we utilize a prospectively collected database of all patients undergoing ULBD from 2015 to 2021 at our institution. We evaluate whether patient specific factors such as sex, age, body mass index (BMI), smoking status, ASA level, number of levels, or previous index level surgery affects durotomy risk. We then determine whether having an intraoperative durotomy affects length of stay (LOS), revision surgery risk, length of time on postoperative pain medications, or Oswestry Disability Index (ODI) scores. RESULTS: In 174 patients undergoing ULBD, there were 11 patients who sustained intraoperative dural tears (6.3%). Utilizing our novel bimanual technique, there was only one patient who required temporary CSF drainage via a lumbar drain. None required revision surgery for CSF leak repair. Durotomy risk was not significantly affected by any patient specific risk factors. Sustaining a durotomy did increase LOS (p=0.033). Intraoperative durotomies did not affect revision surgery risk, or length of time on postoperative pain medications. Utilizing MCID of 12.8 increase in ODI, 70.8% of non-durotomy patients achieved the MCID goal versus 60.0% of durotomy patients. However this trend did not achieve statistical significance (p = 0.605). CONCLUSION: Our novel method of bimanual repair of CSF leaks in full-endoscopic spine surgery appears to be a safe and feasible. There are no patient specific risk factors affecting durotomy risk. Sustaining a durotomy intraoperatively affects LOS but does not significantly alter any other aspect of the postoperative course for patients undergoing ULBD.